Conducting health research : principles, process, and methods - Kviz, Frederick J. (Los Angeles : Sage, 2020)
Conducting Health Research: Principles, Process, and Methods presents an integrated and practical introduction to the principles and strategies for planning, implementing, reporting, and assessing health sciences research. Comprehensive in its breadth and depth, with an accessible writing style, this text prepares students in public health and related fields to be adept researchers and consumers of health research. Through real-world examples and step-by-step guidance, Frederick J. Kviz provides students with the skills they need to: identify and evaluate research strengths and limitations as practitioners; to actually perform the various core aspects of research; and to choose among alternative methods when making decisions about health practice, policy, and future research needs.
The nature and process of research -- Conducting ethically responsible research -- Variables and relationships -- Research design diagrams and components -- Research design validity -- Research designs -- Random sampling and assignment -- The measurement process -- Developing a measurement instrument -- Developing a structured questionnaire -- Writing survey questions -- Survey research methods -- Qualitative research methods -- Secondary analysis and existing data -- The analysis process and reporting results.
Includes bibliographical references and index.
CoEDG
CHS
In English
Keywords: Biomedical Research -- methods; Research Design